A CFD analysis on the effect of vortex finder and cylindrical length on cyclone hydrodynamics and centrifugal forces - Luqman, Chuah A.; Jolius, Gimbun; Thomas, S. Y. Choong; A., Fakhru’l-Razi (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/